2020
DOI: 10.1016/j.vrih.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

VR and AR in human performance research―An NUS experience

Abstract: With the mindset of constant improvement in efficiency and safety in the workspace and training in Singapore, there is a need to explore varying technologies and their capabilities to fulfil this need. The ability of Virtual Reality (VR) and Augmented Reality (AR) to create an immersive experience of tying the virtual and physical environments coupled with information filtering capabilities brings a possibility of introducing this technology into the training process and workspace. This paper surveys current r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The curriculum structure is divided into three levels: (1) The first level is the psychology theory courses, which train students to obtain rigorous research thinking and solid psychology experimental design methods. The students need to understand physiological characteristics and limits of human beings when they ideate HCI solutions.…”
Section: Discussion In the Program Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The curriculum structure is divided into three levels: (1) The first level is the psychology theory courses, which train students to obtain rigorous research thinking and solid psychology experimental design methods. The students need to understand physiological characteristics and limits of human beings when they ideate HCI solutions.…”
Section: Discussion In the Program Reviewmentioning
confidence: 99%
“…However, the traditional academic research-oriented master's degree can no longer meet the education need for interdisciplinary practical talents in UX. Teaching and learning human-computer interaction (HCI) engineering has primary been concerned with feasibility [1,2], the traditional and technically oriented approach to problem solving. As educators are asked to be more innovative in today's commercial and industrial environment, it becomes critical to weigh in on design thinking [3,4] and design doing [5], transdisciplinary domains [6,7], and global context as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, the readiness of students to engage with online learning through information manager or library and information sciences showed that the students were not fully personalized and successful in the decisions about their online educational activities during the COVID-19 pandemic (Rafique et al, 2021), showing that IJAE Page 360 students' skill on computer/internet self-efficacy and online communication self-efficacy relied on gender, age, and levels of degree programs. Some T&L methods adopting digital and technologies in ODL are e-learning (Shahzad et al, 2020), blended learning (Oweis, 2018), virtual reality and augmented reality (Yin et al, 2020, Sholihin et al, 2020, and massive open online course (Notaris et al, 2021, Alhazzani, 2020. The LMSs work in an asynchronous mode only, where the course instructors can upload the course videos and other course contents they desire (Pal & Vanijja, 2020), which are ineffective in handling the pandemic requirements the LMS lacks interactivity and personalization.…”
Section: Open and Distance Learning (Odl)mentioning
confidence: 99%
“…One of the popular areas of research would be intelligence-drive digital factory. This can extend into cyber-physical systems [1], novel augmented and virtual reality applications [2], expert systems [3], and more. These driving technologies help propel new and efficient applications in human-robot interactions within factories of the future.…”
mentioning
confidence: 99%